Pengaruh Model Problem Based Learning dan Motivasi Belajar Terhadap Kemampuan Berpikir Kritis Siswa Pada Mata Pelajaran IPA Kelas V Sekolah Dasar - Triandika, Elsa; Amprasto, Amprasto; Rumanta, Maman (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2023)
The aim of the study was to analyze the effect of the PBL model and learning motivation on students' critical thinking skills in science subject class V, Daru I public elementary school, Tangerang district. Quasi-experimental type of research with 2x2 factorial design. The study population consisted of a sample of 110 students and 76 students sampled using purposive sampling techniques. Research instruments use questionnaires and tests. Data analysis with Two Way Anova using SPPS 22.00 for windows. Hypothesis test result data for the influence of learning models with sig=0.043 values < 0.05 dan F values count 4.226 > 3.873 F table. For student learning motivation sig=0.000 < 0.05 dan F value calculate 190.235 > 3.873 F table. And for the influence of the PBL model with learning motivation sig=0.017 value < 0.05 dan F value count 6.020 > 3.873 F table. The results of the analysis show the impact of the PBL model and student motivation on the critical thinking skills of science students.